THE POTENCY OF BOTANICAL PESTICIDES TO CONTROL ACARINE Tetranychus kanzawai KISHIDA (ACARI: TETRANYCHIDAE) - Affandi, Affandi; Handoko, Handoko (Faculty of Agriculture University of Brawijaya and Indonesian Agronomic Assossiation, 2012)
The research is aimed to confirm the potency of several botanical pesticides to be used as natural biological control and to know the most infective stadium of T. kanzawai was done at Pest and Disease Laboratory of Indonesian Tropical Fruits Research Institute from May to August 2009. A factorial completely randomized design was used in this research. Two factors were observed; first, four kinds of botanical pesticides consist of four treatment levels i.e. extracts of neem, soursop, Siam weed leaves and sterilized water as control.The second was the stadia of T. kanzawai that consist of three levels i.e. larva, nymph and adult. The result showed that Siam weed and soursop leaves extracts caused anti-feedent behavior and decreased mobility at five days after treatment. In addition, exoskeleton of treated T. kanzawai darkened from white, yellowish and bright brown. Extracts of Sourshop and Siam weed leaves caused very high mortality (96.67%) of T. kanzawae compared to neem (79.17%). However, there was no significant difference in mortality rates among the four active stadia of T. kanzawai with average mortality range from 65.63% to 79.38%. Keywords: botanical pesticide, T. kanzawai, control